Lifelong Learning as a Lever for Moral and Democratic Value - Danang Prasetyo; Ricky Santoso Muharam; Hani Subagio; Yuli Hendrika Sugiharti (Indonesian Journal Publisher, 2026)
This paper qualitatively examines the book Lifelong Citizenship: Lifelong Learning as a Lever for Moral and Democratic Value by Dorit Alt and Nirit Raichel using a literature review approach with content analysis. The findings from six chapters are presented as research results and then analyzed to formulate arguments from the reviewer’s perspective, supported by relevant references. The book offers a strong conceptual framework for bridging two significant domains: lifelong learning and democratic citizenship. Based on the analysis of six chapters, the reviewer concludes that the concept of lifelong learning is highly relevant for citizenship studies when linked to 21st-century competencies. The reviewer agrees that dimensions such as personal wellbeing, digital literacy, learning through experience and practice, and social cohesion, inclusion, and justice are closely related to the goals and needs of contemporary citizenship education. Furthermore, the reviewer finds the concept of learning through real-life community practice and assessment for learning particularly compelling. Nevertheless, the discussion originates from authors and findings in European Union countries and the United States, which necessitates adaptation to the cultural context of Asian countries, especially Indonesia. Therefore, this paper emphasizes that not all practices described can be easily implemented in every country due to differences in resources and educational policies.